Historic monuments threatened by coastal hazards at Boca do Rio, Algarve, Portugal - Carrasco, A. Rita (2017)
The coastal stretch of Boca do Rio, western Algarve, Portugal, is experiencing shoreline retreat. Roman ruins are located along the beach section of the coast, and a 17th-century fort is positioned over the cliff section. Both historic monuments are being destroyed by erosion but need to be protected due to their heritage status. Aerial photograph analysis was used to define the evolution of the coast for the period 1945–2001. Shoreline retreat of 0.3 m/year was measured for the sandy coast and 14 mass movements in the cliff face were identified. Considering the rate and style of shoreline evolution, several types of management scenario were evaluated, with the favored measures being the removal of the Roman ruins to a museum and the relocation of the fort inland.